Kebijakan Indonesia Dalam Mewujudkan Industri Hijau (Green Industry) Masa Pemerintahan Presiden Joko Widodo - Asep Saepudin; Sri Muryantini; Herra Dwi Maghfiroh (Eksos LPPM, 2020)
This article aims to describe various policies related to the development of Green Industry in the era of President Joko Widodo. this article is the result of basic research funded by UPN "Veteran" Yogyakarta. The research conducted is qualitative by conducting a study of various policy products produced by president Joko Widodo related to Green Industry. In this article explains that the foundation of Green Industry development has been carried out by president Susilo Bambang Yudhoyono with the issuance of Presidential Decree Number 28 2008 about the objective of long term national industrial development, Industrial Act number 3, 2014 about Industryand Government Regulation number 14, 2015 about the National Industrial Development Master Plan for 2015-2035. Green Industry development is being continued and President Joko Widodo strengthened with the issuance of Presidential Regulation No. 2 of 2018 concerning National Industrial Policy 2015 - 2019. President Joko Widodo has Strengthened on the Standardization of Green industryes, Green Industry facilitation, and the use of Green industryal Products.